FREEDOM OF INFORMATION LAWS IN PAKISTAN: A PERFORMANCE ANALYSIS - Fatima Tu Zahara Arain; Muhammad Akhter Arain; Hyder Ali Memon; Dr Fiaz Hussain (International Journal of Contemporary Issues in Social Sciences, 2023)
The Freedom of Information Act (FOIA), also known as RTI law, allows anyone to request any information they require. An in-depth analysis of different features of the law of information prevailing in Pakistan is the scope of this paper. The paper discusses the role played by the public bodies, PIOs, and Information Commission in disseminating information. Along with the challenges in the way of FOI implementation and explores the policies to overcome these challenges. This paper highlights the long-term social, economic and political impacts of RTI laws in Pakistan. The paper employs a qualitative approach to achieve results. It includes interviews conducted by journalists, academicians, politicians, government workers and students. The results acknowledge that FOI is a fundamental law as it promotes transparency and accountability without discriminating against individuals, whether disabled or not. However, the paper argues for a need for proper awareness and enforcement of the Act by pointing out the shortcomings on the part of stakeholders. It suggests the need for joint action by the government, media, bureaucracy, political parties and the public to overcome bad governance and corruption challenges. The paper emphasizes proper measures to overcome the weaknesses of Information Commissions, public bodies and PIOs related to proper training and workshops, access to records, coordination between departments, and checks and balances. Thus the paper argues that with FOIA, freedom of information and transparency can be ensured in Pakistan.